1982
DOI: 10.1152/jappl.1982.53.5.1291
|View full text |Cite
|
Sign up to set email alerts
|

Effects on heat tolerance of physical training in water and on land

Abstract: A 4-wk training program was undertaken by 15 untrained non-heat-acclimated males who were divided into three groups matched on maximal aerobic capacity (VO2max) and trained either in water or on land to determine how physical training (PT) in these different media affects heat tolerance. Subjects trained on a cycle ergometer for 1 h/day, 5 days/wk at 75% VO2max, with the exercise intensity progressively increased to maintain a constant training stimulus. Group I exercised on land, whereas groups II and III exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 7 publications
4
43
1
Order By: Relevance
“…Therefore, it was uncertain if SIT performed in the heat would provide a sufficient stimulus to promote heat acclimation. The increases we observed were lower than those (,1˚C) of other studies that have shown heat acclimation adaptations associated with elevated core body temperatures (Avellini et al, 1982;Regan et al, 1996). Our participants not only experienced smaller increases in core temperature than those in the cited studies, they also were exposed to these elevated core temperatures for less time; SIT sessions lasted ,30-40 min (total time including warm-up, etc.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Therefore, it was uncertain if SIT performed in the heat would provide a sufficient stimulus to promote heat acclimation. The increases we observed were lower than those (,1˚C) of other studies that have shown heat acclimation adaptations associated with elevated core body temperatures (Avellini et al, 1982;Regan et al, 1996). Our participants not only experienced smaller increases in core temperature than those in the cited studies, they also were exposed to these elevated core temperatures for less time; SIT sessions lasted ,30-40 min (total time including warm-up, etc.…”
Section: Discussioncontrasting
confidence: 68%
“…The mechanism for heat acclimation adaptations has historically been attributed to chronic exposure to elevated core body temperature (Avellini et al, 1982;Piwonka, Robinson, Gay, & Manalis, 1965) and, to a lesser extent, skin temperature (Regan et al, 1996). During the SIT sessions, our participants experienced increases in T re of 0.5 ¡ 0.2˚C (0.6 ¡ 0.2˚C for hot group and 0.4 ¡ 0.1˚C for temperate group) from baseline to the end of the last WAnT on the first day of SIT and 0.8 ¡ 0.2˚C (0.9 ¡ 0.1˚C for hot group and 0.7 ¡ 0.3˚C for temperate group) from baseline to the end of the last WAnT on the final day of SIT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term ®tness has also been associated with an increased tolerance to exercise in the heat in both longitudinal training (Avellini et al 1982;Gisol® and Robinson 1969) and cross-sectional (Piwonka and Robinson 1967) studies. For these reasons, improvements in aerobic ®tness have been associated with a reduction in physiological strain and increased performance time during exercise in the heat, and physical training programs have been used as a method of heat acclimation (Armstrong and Pandolf 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Henane et al (1977) suggest that training must increase O 2 max by approximately 15% to induce a level of physiological strain that would result in signi®cant adaptations to heat. The degree of adaptation to heat stress may also depend on both the magnitude and the duration of hyperthermia in the body (Avellini et al 1982;Fox et al 1963). Subjects in the present study did increase their T re approximately 1.2°C over the hour of exercise, though with a relatively short time at a maintained state of hyperthermia.…”
Section: Discussionmentioning
confidence: 99%